The gut microbiome-immunity-virus axis in lepidopteran antiviral defense - Abrar Muhammad; Chao Sun; Yongqi Shao (Current Opinion in Insect Science, 2026)

AM fungal and rhizobacteria jointly enhance vegetable waste decomposition in soils and harvest environmental and agronomic benefits in dryland - Muhammad Maqsood Ur Rehman; Sidra Khattak; Ling Zhao; Yun-Li Xiao; Ying Zhu; Awais Iqbal; Rafi Ullah; Nang Chang; Muhammad Abrar; Jian-Ming Li; Hao Sun; Adnan Khan; et al. (Agriculture, Ecosystems & Environment, 2026)

Dynamics of coral community structure after the 2016 mass bleaching event along the Western Coast of Sumatra, Indonesia - Rikoh Manogar Siringoringo; Dietriech Geoffrey Bengen; I. Wayan Nurjaya; Beginer Subhan; Giyanto; Risandi Dwirama Putra; Muhammad Abrar; Ni Wayan Purnama Sari; Eka Widya Utami; La Ode Alifatri; Sam Wouthuyzen; Fadhlan Basiluddim Rahmat; et al. (Regional Studies in Marine Science, 2026)

Integrative Network Pharmacology and Molecular Dynamics Simulation Uncover Key Molecular Targets of Curcumin and Its Derivatives in Colorectal Cancer - Usama Ilahi; Muhammad Suleman; Abrar Mohammad Sayaf; Muhammad Rizwan; Fazal Akbar; Zafar Ali; Haji Khan; Zahid Hussain; Mohammad Ali; Hadi M. Yassine; Abdullah A. Shaito; Sergio Crovella (Journal of Pharmaceutical Innovation, 2026)

From multi-omics insights to single-strain proof: How traditional agricultural system enhances fish flavor via the microbiome-gut-muscle axis - Xiaoqiang Shen; Xiaoyu Lei; Huarui Zhang; Enhui Guo; Lichao Chen; Chao Sun; Abrar Muhammad; Yongqi Shao (Bioresource Technology, 2026)

Evaluation of Probiotic Metabolites Mediated Antimicrobial Activity and Inhibition of Virulence Factors in Avian Pathogenic Escherichia Coli - Kanchan Thapa; Anna Phan; Chuan-Wei Tung; Muhammad Abrar Hashmi; Debabrata Biswas (Probiotics and Antimicrobial Proteins, 2026)

Physics-informed graph neural networks for transverse momentum estimation in CMS trigger systems - Md Abrar Jahin; Shahriar Soudeep; M.F. Mridha; Muhammad Mostafa Monowar; Md Abdul Hamid (Computer Physics Communications, 2026)

A new ecological index for assessing benthic invertebrate assemblages in tropical coral reef ecosystems - Hadiyanto Hadiyanto; Indra Bayu Vimono; Hendrik Alexander William Cappenberg; Ludi Parwadani Aji; Teddy Triandiza; Ana Setyastuti; Ismiliana Wirawati; Ernawati Widyastuti; Rianta Pratiwi; Putri Saphira Ibrahim; Tyani Fitrian; Allsay Kitsash Addifisyukha Cintra; et al. (Aquatic Sciences, 2026)

Microplastics and pathogen risk across ecosystems: From biofilm to antimicrobial resistance and host susceptibility - Feroz Ahmad; Chao Sun; Abrar Muhammad; Yongqi Shao (Environmental Pollution, 2026)

Two decades of coral monitoring reveal thermal stress thresholds on Indonesian reefs - Tries B. Razak; Cut Aja Gita Alisa; Muhammad Abrar; Rizya Ardiwijaya; Imam Bachtiar; Ravienkha R. Budaya; Dan Exton; Giyanto; Aradea R. Hakim; Muhammad Erdi Lazuardi; M. Munasik; Efin Muttaqin; et al. (Biological Conservation, 2026)

Adaptive spectral indices for mangrove and industrial area detection to strengthen blue carbon assessment in coastal regions - Dimas Danar Dewa; Ugay Sugarmansyah; Heri Apriyanto; Sherafina Reni Cahayanti; Nugroho Adi Sasongko; Warseno Warseno; Yanuar Iman Dwiananto; Anissa Dewi Suryaningtyas; Muhammad Abrar Rizqullah (Spatial Information Research, 2026)

Paleodietary inferences of the Pleistocene (Pinjor Formation) ungulates from district Gujrat using mesowear analysis - Abrar Hussain; Muhammad Akbar Khan; Muhammad Asim; Sayyed Ghyour Abbas; Muhammad Adeeb Babar; Khalid Mahmood (Quaternary International, 2026)

Global composite drought indices for investigating the effects of climate-driven drought on major crop water requirements - Muhammad Abrar Faiz; Liangliang Zhang; Dong Liu; Yongqiang Zhang; Mo Li; Farah Naz (Science China Earth Sciences, 2026)

Targeting 3Cpro of Enterovirus D68 with Medicinal Phytocompounds Using Structure-Based Molecular Screening and Molecular Simulation Approaches to Rescue the Host Immune Response - Muhammad Suleman; Abrar Mohammad Sayaf; Fazal Akbar; Mohammed Alissa; Ghadah S. Abusalim; Ghada M. Alnafesah; Kar Kheng Yeoh; Sergio Crovella; Hadi M. Yassine (Journal of Pharmaceutical Innovation, 2026)

Artemisia absinthium attenuates hepatic fibrosis in mice by suppressing hepatic stellate cells activation and modulating inflammatory chemokine signaling - Rabbia Manzoor; Iram Gull; Abrar Ahmed; Tuba Ghulam Hussain; Ubaida Hussain; Muhammad Shahbaz Aslam (Cell Biochemistry and Biophysics, 2026)

Corrigendum to “global research on the air quality status in response to the electrification of vehicles” [Science of the Total Environment, 795, (2021), 148861] - Yansong Bao; Khalid Mehmood; Saifullah; Muhammad Yaseen; Saad Dahlawi; Muhammad Mohsin Abrar; Shah Fahad (Science of The Total Environment, 2026)

Cereal-legume intercropping stabilizes yield and economic advantages under variable rainfall in semiarid rainfed environment - Wei Wang; Bao-Zhong Wang; Wei Zhang; Meng-Ying Li; Jian-Ming Li; Sheng-Jun Ji; Muhammad Abrar; Muhammad Maqsood Ur Rehman; Wasim Khan; Hong-Yan Tao; Mohamed S. Sheteiwy; Wen-Ying Wang; et al. (European Journal of Agronomy, 2026)

Hydrogeochemical dynamics of sub-Himalayan springs: assessing health risks and environmental impacts in Muzaffarabad, Pakistan - Mansoor Awan; Abrar Niaz; Ahmer Bilal; Muhammad Saleem Mughal; Li Yang; Xingyue Qu; Ali Yousaf Khan (Carbonates and Evaporites, 2026)

Convolutional autoencoders for low probability of detection constrained underwater acoustic communications - Mohsin Abrar Khan; Songzuo Liu; Muhammad Bilal; Ahmad Hassan (Ocean Engineering, 2026)

Hybrid Gaussian process regression-based harmony assessment in a water–land–energy–food–carbon-emission coupled system - Chunqing Wang; Liangliang Zhang; Dong Liu; Mo Li; Muhammad Abrar Faiz; Tianxiao Li; Song Cui; Muhammad Imran Khan (Journal of Hydrology, 2026)

Ecological and functional dynamics of gut microbiota in the model insect, silkworm Bombyx mori - Abrar Muhammad; Chao Sun; Yongqi Shao (World Journal of Microbiology and Biotechnology, 2026)

A comprehensive insight on the bioactive phytochemicals and pharmacological propensities of Ficus benghalensis L.: a reservoir for modern drug discovery - Sulaman Yaqub; Muhammad Islam; Hamid Saeed; Abrar Ahmad; Khurram Aamir; Rida Naeem; Meerab Tanveer (Phytochemistry Reviews, 2026)

Integrated assessment of groundwater potential and quality in a seismically active Himalayan city: a case study from Muzaffarabad, Pakistan - Raja Dilawar Sajjad; Abrar Niaz; Ahmer Bilal; Muhammad Tayyib Riaz; Ali Yousaf Khan; Xiwu Luan (Environmental Geochemistry and Health, 2026)

Simulation and Optimization of H2, CO, CO2, and CH4 Obtained from the Co-pyrolysis of Date Seeds and Tire Plastic Waste - Lisandra Rocha-Meneses; Muhammad Shahbaz; Abrar Inayat; Mario Luna-delRisco (BioEnergy Research, 2025)

GTG-ACO: Graph Transformer Guided Ant Colony Optimization for learning heuristics and pheromone dynamics for combinatorial optimization - Abrar Rahman Abir; Muhammad Ali Nayeem; M. Sohel Rahman; Md Adnan Arefeen (Swarm and Evolutionary Computation, 2025)

Corrigendum to “Spatial distribution of juvenile corals (Scleractinia) in the coastal and small islands of Sumatra, Indonesia” [Reg. Stud. Mar. Sci. 80 (2024) 103857] - Muhammad Abrar; Dietriech G. Bengen; Neviaty P. Zamani; Suharsono; Giyanto; Risandi D. Putra; Ni Wayan P. Sari; Rikoh M. Siringoringo; Tri A. Hadi; Rizkie S. Utama; Bambang Hermanto; Ucu Y. Arbi; et al. (Regional Studies in Marine Science, 2025)

Corrigendum to “Spatio- temporal juvenile corals (Scleractinia) following the 2016 coral bleaching event at the Pieh Islands Marine Tourism Park (PIMTP), West Sumatra Province, Indonesia” [Reg. Stud. Mar. Sci. 75 (2024) 103533] - Muhammad Abrar; Dietriech G. Bengen; Neviaty P. Zamani; Suharsono; Risandi Dwirama Putra; Ni Wayan Purnama Sari; Rikoh M. Siringoringo; Tri Aryono Hadi; Giyanto; Raden Sutiadi; Ana Faricha; Yuwanda Ilham; et al. (Regional Studies in Marine Science, 2025)

Synergies and struggles: Water security and climate action in South Asia’s quest for SDG 6 and SDG 13 - Faisal Baig; Assaad Kassem; Md. Zishan Akhter; Saifudeen Kabeer; Muhammad Abrar Faiz; Mirza Farrukh Baig; Mohsen Sherif (Gondwana Research, 2025)

Biochar Amendment Improved Growth and Yield of Fragrant Rice and Reduced Arsenic (As) Accumulation under As-contaminated Irrigation Water - Umair Ashraf; Talat Mansha; Shakeel Ahmad Anjum; James DeDecker; Abrar Hussain; Fahd Rasul; Muhmmad Abrar; Muhammad Ishfaq (Water, Air, & Soil Pollution, 2025)

Simulation and Optimisation of Bio-oil, Biochar, and Syngas Obtained from Pyrolysis and Co-pyrolysis of Date Seeds and Tire Plastic Waste - Lisandra Rocha-Meneses; Anjana Hari; Muhammad Shahbaz; Abrar Inayat; Mario Luna-delRisco (Circular Economy and Sustainability, 2025)

Sedimentology and biostratigraphy of the Cretaceous–Paleocene successions in Northern Pakistan: evidence from the Hazara, Kala Chitta, Potwar, and Kohat Basins - Syed Kamran Ali; Hafiz Sohaib Bashir; Asim Qadir; Muhammad Saleem Mughal; Khurram Iqbal; Abrar Niaz; Khawaja Umair Majeed (Carbonates and Evaporites, 2025)

Casuarinin modulates renin-angiotensin-aldosterone system to counter ephedrine-induced myocardial damage in rats - Hesham M. Hassan; Muhammad Faisal Hayat; Ali Akbar; Azka Zafar; Khalid J. Alzahrani; Fuad M. Alzahrani; Abrar Aljohani (Toxicon, 2025)

Amplification effects of AM fungus and rhizobacteria on carbon efficiency in wheat-soil system under drought stress via priming rhizosphere activities - Muhammad Maqsood Ur Rehman; Ling Zhao; Sidra Khattak; Yun-Li Xiao; Awais Iqbal; Wasim Khan; Muhammad Abrar; Zheng-Guo Cheng; Shi-Sheng Li; Asfa Batool; Ying Zhu; You-Cai Xiong (Applied Soil Ecology, 2025)

Advancement in hydrogen production, application and strategy towards sustainable energy: Malaysian case study - Mariam Ameen; Huei Yeong Lim; Haswin Kaur; Nur’aini Raman Yusuf; David Onoja Patrick; Muhammad Shahbaz; Abrar Inayat; Suzana Yusup (Process Safety and Environmental Protection, 2025)

Comparative assessment of biochar and vermicompost on chromium bioavailability and stress alleviation in tomato (Solanum lycopersicum) - Jamaluddin Kabir; Muhammad Ansar Farooq; Shumaila Parvez; Aamir Alaud Din; Ghulam Abbas; Minggang Xu; Muhammad Mohsin Abrar (Journal of Soils and Sediments, 2025)

Zero-carbon solution: Microalgae as a low-cost feedstock for fuel production and carbon sequestration - Moeen Ali Rashad; Farrukh Jamil; Murid Hussain; Abrar Inayat; Parveen Akhter; Muhammad Haris Hamayun; Ali Ahsan; Young-Kwon Park (Critical Reviews in Environmental Science and Technology, 2025)

New AI explained and validated deep learning approaches to accurately predict diabetes - Ifra Shaheen; Nadeem Javaid; Nabil Alrajeh; Yousra Asim; Syed Muhammad Abrar Akber (Medical & Biological Engineering & Computing, 2025)

Stage-dependent synergistic impacts of AM fungi and rhizobacteria on phytohormone mediation and field productivity in dryland maize - Muhammad Abrar; Ying Zhu; Wen-Shan Li; Muhammad Aqeel; Umair Ashraf; Muhammad Maqsood Ur Rehman; Jian-Ming Li; Xiao-Fang Gong; Wasim Khan; Wei Wang; You-Cai Xiong (Field Crops Research, 2025)

From bias to accuracy: Transforming satellite precipitation data in arid regions with machine learning and topographical insights - Faisal Baig; Luqman Ali; Muhammad Abrar Faiz; Haonan Chen; Mohsen Sherif (Journal of Hydrology, 2025)

Evaluating Vertical Distribution of Soil Salinity Patterns Across Multiple Soil Depths in a Semi-Arid Dry Region - Qambar Baloch; Kashif Ali Kubar; Punhoon Khan Korai; Shahmir Ali Kalhoro; Muhammad Bilawal Junaid; Muneer Ahmed Baloch; Zia-ul-hassan; Jawaher Alkahtani; Muhammad Abrar (Journal of Soil Science and Plant Nutrition, 2025)

Revisiting the composite drought index for improving drought monitoring - Muhammad Abrar Faiz; Liangliang Zhang; Dong Liu; Ning Ma; Mo Li; Zhaoqiang Zhou; Faisal Baig; Tianxiao Li; Song Cui (Journal of Hydrology, 2025)

Amelioration of pain and adjuvant-induced arthritis by syringic acid via modulation of behavioral parameters and inflammatory mediators i.e. TNF-α, Interleukins, MCP-1, NF-kB and COX-2 - Noviara Saleem; Syed Atif Raza; Alamgeer; Muhammad Khalil-ur-Rehman; Rukhsana Anwar; Abrar Ahmed; Hafiz Muhammad Irfan (Inflammopharmacology, 2025)

Exploring Lamiaceae-derived bioactive compounds as nature’s arsenal for sustainable pest management - Muhammad Ali; Abrar Muhammad; Zemian Lin; Hai He; Yu Zhang (Phytochemistry Reviews, 2025)

Organic carbon and nitrogen accrual evidenced by the underpinning protection mechanisms in soil profile following contrasting 35-year fertilization regimes - Muhammad Mohsin Abrar; Muhammad Ahmed Waqas; Khalid Mehmood; Ruqin Fan; Baoku Zhou; Xingzhu Ma; Sun Nan; Jianjun Du; Minggang Xu (Journal of Environmental Management, 2025)

Appraisal of the physio-biochemical efficacy of exogenously applied natural and synthetic sources of plant growth stimulants in modulating drought stress tolerance in maize (Zea mays L.) - Abrar Ahmad; Nudrat Aisha Akram; Muhammad Ashraf (Acta Physiologiae Plantarum, 2025)

Repurposing doxycycline for the inhibition of monkeypox virus DNA polymerase: a comprehensive computational study - Muhammad Abrar Yousaf; Maurice Michel; Abeedha Tu-Allah Khan; Misbah Noreen; Saddia Bano (In Silico Pharmacology, 2025)

Identification and quantification of selected heavy metals by ICP-OES in skin whitening creams marketed in Pakistan - Mirza Nadeem Ahmad; Umm-e-Khadija Ashraf; Muhammad Naveed Anjum; Shumaila Kiran; Shazia Abrar; Muhammad Fayyaz Farid (Environmental Monitoring and Assessment, 2025)

Prevalence and herd-level risk factors associated with Brucella infection in smallholders keeping large ruminants - Abrar Hussain; Sabir Hussain; Mamoona Chaudhry; Muhammad Asif Ali; Ibrahim Elsohaby; Ubaid-ur-Rehman Zia; Olivier Sparagano (Research in Veterinary Science, 2025)

Advances in non-thermal technologies: A revolutionary approach to controlling microbial deterioration, enzymatic activity, and maintaining other quality parameters of fresh stone fruits and their processed products - Kashmala Chaudhary; Samran Khalid; Ammar B. Altemimi; Saqib Abrar; Sadia Ansar; Nabila Aslam; Mudassar Hussain; Rana Muhammad Aadil (Food Chemistry, 2025)

Probiotic potential and biotechnological characterization of the selected enterococcal strains - Abrar Hussain; Muhammad Shakeel; Muhammad Tanweer Khan; Syed Abid Ali (Food Bioscience, 2025)

Correction: Symmetrical Ligand’s Fabricated Porous Silicon Surface Based Photoluminescence Sensor for Metal Detection and Entrapment - Muhammad Saleem; Abrar Hussain; Salah Uddin Khan; Sajjad Haider; Ki Hwan Lee; Sang Hyun Park (Journal of Fluorescence, 2024)

Correction: Synthesis, Invitro Cytotoxic Activity and Optical Analysis of Substituted Schiff Base Derivatives - Muhammad Saleem; Abrar Hussain; Muhammad Hanif; Hufsa Ahmad; Salah Uddin Khan; Sajjad Haider; Muhammad Rafiq; Rizwan Nasir Paracha; Sang Hyun Park (Journal of Fluorescence, 2024)

Correction: Ratiometric Fluorescence and Chromogenic Probe for Trace Detection of Selected Transition Metals - Muhammad Saleem; Abrar Hussain; Muhammad Rauf; Salah Uddin Khan; Sajjad Haider; Muhammad Hanif; Muhammad Rafiq; Sang Hyun Park (Journal of Fluorescence, 2024)

Enhancing renewable energy evaluation: Utilizing complex picture fuzzy frank aggregation operators in multi-attribute group decision-making - Abrar Hussain; Shi Yin; Kifayat Ullah; Muhammad Waqas; Tapan Senapati; Domokos Esztergár-Kiss; Sarbast Moslem (Sustainable Cities and Society, 2024)

Spatial distribution of juvenile corals (Scleractinia) in the coastal and small islands of Sumatra, Indonesia - Muhammad Abrar; Dietriech G. Bengen; Neviaty P. Zamani; Suharsono; Giyanto; Risandi D. Putra; Ni Wayan. P. Sari; Rikoh M. Siringoringo; Tri A. Hadi; Rizkie S. Utama; Bambang Hermanto; Ucu Y. Arbi; et al. (Regional Studies in Marine Science, 2024)

Spatio- temporal juvenile corals (Scleractinia) following the 2016 coral bleaching event at the Pieh Islands Marine Tourism Park (PIMTP), West Sumatra Province, Indonesia - Muhammad Abrar; Dietriech G. Bengen; Neviaty P. Zamani; Suharsono; Risandi Dwirama Putra; Ni Wayan Purnama Sari; Rikoh M. Siringoringo; Tri Aryono Hadi; Giyanto; Raden Sutiadi; Ana Faricha; Yuwanda Ilham; et al. (Regional Studies in Marine Science, 2024)

Low mercury risks in paddy soils across the Pakistan - Muhammad Wajahat Aslam; Bo Meng; Waqar Ali; Muhammad Mohsin Abrar; Mahmoud A. Abdelhafiz; Xinbin Feng (Science of The Total Environment, 2024)

Inhibition of Monkeypox Virus DNA Polymerase Using Moringa oleifera Phytochemicals: Computational Studies of Drug-Likeness, Molecular Docking, Molecular Dynamics Simulation and Density Functional Theory - Muhammad Abrar Yousaf; Shefin Basheera; Sreekumar Sivanandan (Indian Journal of Microbiology, 2024)

Prospecting Ulva lactuca seaweed in Java Island, Indonesia, as a candidate resource for industrial applications - Rizfi Fariz Pari; Uju; Agung Tri Wijayanta; Wahyu Ramadhan; Safrina Dyah Hardiningtyas; Kiki Adi Kurnia; Mochamad Lutfi Firmansyah; Arinal Hana; Muhammad Naufal Abrar; Rie Wakabayashi; Noriho Kamiya; Masahiro Goto (Fisheries Science, 2024)

Satellite-based rainwater harvesting sites assessment for Dera Ghazi Khan, Punjab, Pakistan - Samman Aziz; Muhammad Y. S. Dasti; Mashal Abrar; Faisal Mumtaz; Aqil Tariq (Environmental Science and Pollution Research, 2024)

Strengthening oil pollution monitoring system in aquatic environment through development of IoT-based Oil-Water Separator Device - Faisal Budiman; Abrar Ismardi; Tri Hardinah; Rayi Muhammad; Nurwijayadi; Aris Hartaman; Agus Nurhidayat; Iman H.S. Sasto; Ignasius D.A. Sutapa (Ecohydrology & Hydrobiology, 2024)

Synthesis, Invitro Cytotoxic Activity and Optical Analysis of Substituted Schiff Base Derivatives - Muhammad Saleem; Abrar Hussain; Muhammad Hanif; Hufsa Ahmad; Salah Uddin Khan; Sajjad Haider; Muhammad Rafiq; Rizwan Nasir Paracha; Sang Hyun Park (Journal of Fluorescence, 2024)

Assessing the quality and eco-beneficial microbes in the use of silkworm excrement compost - Xiaoqiang Shen; Jintao He; Nan Zhang; Yu Li; Xiaoyu Lei; Chao Sun; Abrar Muhammad; Yongqi Shao (Waste Management, 2024)

Repurposing FDA approved drugs against monkeypox virus DNA dependent RNA polymerase: virtual screening, normal mode analysis and molecular dynamics simulation studies - Ahmad Abdul Salam Khan; Muhammad Abrar Yousaf; Jahanzaib Azhar; Muhammad Faisal Maqbool; Ruqia Bibi (VirusDisease, 2024)

Berberine ameliorates the progression of primary sclerosing cholangitis by activating farnesoid X receptor - Hassan Hameed; Nida Irshad; Muhammad Abrar Yousaf; Sidra Mumtaz; Imran Sohail (Cell Biochemistry and Biophysics, 2024)

Measurement and analysis of regional water-energy-food nexus resilience with an improved hybrid kernel extreme learning machine model based on a dung beetle optimization algorithm - Zhiqin Zhang; Liangliang Zhang; Dong Liu; Nan Sun; Mo Li; Muhammad Abrar Faiz; Tianxiao Li; Song Cui; Muhammad Imran Khan (Agricultural Systems, 2024)

Utilizing sludge-based activated carbon for targeted leachate mitigation in wastewater treatment - Sarah Mushtaq; Farrukh Jamil; Murid Hussain; Abrar Inayat; Khaliq Majeed; Parveen Akhter; Muhammad Shahzad Khurram; Abdallah Shanableh; Young Mo Kim; Young-Kwon Park (Environmental Research, 2024)

Symmetrical Ligand’s Fabricated Porous Silicon Surface Based Photoluminescence Sensor for Metal Detection and Entrapment - Muhammad Saleem; Abrar Hussain; Salah Uddin Khan; Sajjad Haider; Ki Hwan Lee; Sang Hyun Park (Journal of Fluorescence, 2024)

Spatio-temporal variation in progression rates of black band disease between Pramuka Island and Pari Island of the Seribu Islands, Indonesia - Ofri Johan Ofri; Rendy Ginanjar; Agustin Rustam; Idil Ardi; Lili Sholichah; Rita Rachmawati; Rikoh Manogar Siringoringo; Muhammad Abrar; Ni Wayan Purnama Sari; Giyanto; Andrias Steward Samusamu; Nani Ingrid Undap; et al. (Frontiers in Marine Science, 2024)
Black band disease (BBD) is one of the oldest recognized diseases of scleractinian corals. This disease is little known on the variation of progression rates across relatively small spatial scales and how local variations in the environment can impact prevalence and spread. The purpose of this study was to explore the progression of BBD on genus Montipora in relation to spatio-temporal environmental parameters in two islands of the Seribu Islands, North Jakarta, Indonesia during dry season and rainy season. Monthly underwater pictures were taken for determining the progress of disease level. Interestingly, the progression rate of the disease recorded at Pramuka Island was higher (8.10 cm 2 day -1 ) than the one at Pari Island (3.79 cm 2 day -1 ). In Pramuka Island, the infected corals had almost 89% of the dead surface, compared to only 68% at Pari Island. Similar to other studies in the region, we confirmed that the disease progressed faster during the dry season, where the environmental parameters, such as temperature, light intensity, and phosphate, were starting to increase, while total organic matter, current flow rates, and turbidity were lower. Progression of the disease was significantly different between seasons ( p <0.001), but not between sites ( p =0.118). Therefore, the progress of BBD has a higher impact at the more populated Pramuka island than at the less populated Pari Island, in addition to the influence of environmental parameters on coral vulnerability to diseases.

How accurate are the machine learning models in improving monthly rainfall prediction in hyper arid environment? - Faisal Baig; Luqman Ali; Muhammad Abrar Faiz; Haonan Chen; Mohsen Sherif (Journal of Hydrology, 2024)

Microorganism-mediated biodegradation for effective management and/or removal of micro-plastics from the environment: a comprehensive review - Hassan Zahid; Nimra Afzal; Muhammad Maaz Arif; Mahnoor Zahid; Samia Nawab; Malik Muhammad Qasim; Farhat Naseem Alvi; Sumbal Nazir; Ishrat Perveen; Naaz Abbas; Yasar Saleem; Sania Mazhar; et al. (Archives of Microbiology, 2024)

Ratiometric Fluorescence and Chromogenic Probe for Trace Detection of Selected Transition Metals - Muhammad Saleem; Abrar Hussain; Muhammad Rauf; Salah Uddin Khan; Sajjad Haider; Muhammad Hanif; Muhammad Rafiq; Sang Hyun Park (Journal of Fluorescence, 2024)

2D MXenes and their composites; design, synthesis, and environmental sensing applications - Naseer Ahmad; Sufian Rasheed; Abrar Mohyuddin; Batool Fatima; Muhammad Ikram Nabeel; Muhammad Tariq Riaz; Muhammad Najam-ul-Haq; Dilshad Hussain (Chemosphere, 2024)

Above-and below-ground feedback loop of maize is jointly enhanced by plant growth-promoting rhizobacteria and arbuscular mycorrhizal fungi in drier soil - Wasim Khan; Ying Zhu; Aziz Khan; Ling Zhao; Yu-Miao Yang; Ning Wang; Meng Hao; Yue Ma; Jaya Nepal; Fazal Ullah; Muhammad Maqsood Ur Rehman; Muhammad Abrar; et al. (Science of The Total Environment, 2024)

Shining in or fading out: Do precious metals sparkle for cryptocurrencies? - Afsheen Abrar; Muhammad Abubakr Naeem; Sitara Karim; Brian M. Lucey; Samuel A. Vigne (Resources Policy, 2024)

Silicon-nanoparticles loaded biochar for soil arsenic immobilization and alleviation of phytotoxicity in barley: Implications for human health risk - Muhammad Asif Naeem; Abrar Shabbir; Muhammad Imran; Sajjad Ahmad; Muhammad Shahid; Behzad Murtaza; Muhammad Amjad; Waqas-ud-Din Khan (Environmental Science and Pollution Research, 2024)

Design and Exploration of Benzene Like Azobis Triazoles for Long-range Push-Pull Photo-Switching Attributes - Abrar U. Hassan; Sajjad H. Sumrra; Muhammad Zubair; Ayesha Mohyuddin; Ghulam Mustafa (Journal of Fluorescence, 2023)

Silver hybridized polymer nanocomposite for efficient encapsulation of toxic dye from aqueous solution - Muhammad Amjad; Ayesha Mohyuddin; Wajad Ulfat; Saeed Ahmed; Abrar Ul Hassan (Nanotechnology for Environmental Engineering, 2023)

Production, purification, and characterization of p-diphenol oxidase (PDO) enzyme from lignolytic fungal isolate Schizophyllum commune MF-O5 - Muhammad Faheem; Syed Ali Imran Bokhari; Muhammad Arshad Malik; Bashir Ahmad; Muhammad Riaz; Nafeesa Zahid; Adil Hussain; Abdul Ghani; Hanif Ullah; Waseem Shah; Rashid Mehmood; Khurshid Ahmad; et al. (Folia Microbiologica, 2023)

Deep-Neural-Network-Based Receiver Design for Downlink Non-Orthogonal Multiple-Access Underwater Acoustic Communication - Habib Hussain Zuberi; Songzuo Liu; Muhammad Bilal; Ayman Alharbi; Amar Jaffar; Syed Agha Hussnain Mohsan; Abdulaziz Miyajan; Mohsin Abrar Khan (Journal of Marine Science and Engineering, 2023)
The excavation of the ocean has led to the submersion of numerous autonomous vehicles and sensors. Hence, there is a growing need for multi-user underwater acoustic communication. On the other hand, due to the limited bandwidth of the underwater acoustic channel, downlink non-orthogonal multiple access (NOMA) is one of the fundamental pieces of technology for solving the problem of limited bandwidth, and it is expected to be beneficial for many modern wireless underwater acoustic applications. NOMA downlink underwater acoustic communication (UWA) is accomplished by broadcasting data symbols from a source station to several users, which uses superimposed coding with variable power levels to enable detection through successive interference cancellation (SIC) receivers. Nevertheless, comprehensive information of the channel condition and channel state information (CSI) are both essential for SIC receivers, but they can be difficult to obtain, particularly in an underwater environment. To address this critical issue, this research proposes downlink underwater acoustic communication using a deep neural network utilizing a 1D convolution neural network (CNN). Two cases are considered for the proposed system in the first case: in the first case, two users with different power levels and distances from the transmitter employ BPSK and QPSK modulations to support multi-user communication, while, in the second case, three users employ BPSK modulation. Users far from the base station receive the most power. The base station uses superimposed coding. The BELLHOP ray-tracing algorithm is utilized to generate the training dataset with user depth and range modifications. For training the model, a composite signal passes through the samples of the UWA channel and is fed to the model along with labels. The DNN receiver learns the characteristic of the UWA channel and does not depend on CSI. The testing CIR is used to evaluate the trained model. The results are compared to the traditional SIC receiver. The DNN-based DL NOMA underwater acoustic receiver outperformed the SIC receiver in terms of BER in simulation results for all the modulation orders.

Groundwater vulnerability to contamination in the gulf cooperation council region: A review - Faisal Baig; Mohsen Sherif; Ahmed Sefelnasr; Muhammad Abrar Faiz (Groundwater for Sustainable Development, 2023)

Groundwater vulnerability assessment to pollution using GIS-based DRASTIC and GOD methods in Araihazar upazila of Narayanganj district, Bangladesh - Muhammad Abu Sayed; A.S.M. Maksud Kamal; Abrar Hossain; Mahmudul Hasan; Mahfuzur R Khan; Kazi Matin Uddin Ahmed; Peter S.K. Knappett (Groundwater for Sustainable Development, 2023)

Assessing total erythrocyte count as a potential attribute for estimating hemoglobin in Cholistani cattle - Umer Farooq; Musadiq Idris; Nouman Sajjad; Muhammad Abrar Afzal (Tropical Animal Health and Production, 2023)

Unearthing research trends in emissions and sustainable development: Potential implications for future directions - Khalid Mehmood; Saifullah; Xuchun Qiu; Muhammad Mohsin Abrar (Gondwana Research, 2023)

Influence of Co3O4-based catalysts on N2O catalytic decomposition and NO conversion - Abrar Inayat; Lisandra Rocha-Meneses; Muhammad Ayoub; Sami Ullah; Ahmad Z. Abdullah; Salman R. Naqvi; Aamir H. Bhat (Environmental Science and Pollution Research, 2023)

Municipal solid waste treatment for bioenergy and resource production: Potential technologies, techno-economic-environmental aspects and implications of membrane-based recovery - Naila Amin; Muhammad Aslam; Zakir khan; Muhammad Yasin; Shakhawat Hossain; Muhammad Kashif Shahid; Abrar Inayat; Ahmed Samir; Rizwan Ahmad; Mohammad N. Murshed; Muhammad Shahzad Khurram; Mohamed E. El Sayed; et al. (Chemosphere, 2023)

Biogenic synthesis and characterization of ZnO nanoparticles for degradation of synthetic dyes: A sustainable environmental cleaner approach - Atizaz Rasool; Shumaila Kiran; Tahsin Gulzar; Shazia Abrar; Abdul Ghaffar; Muhammad Shahid; Sofia Nosheen; Saba Naz (Journal of Cleaner Production, 2023)

Time series analysis for droughts characteristics response to propagation - Muhammad Abrar Faiz; Yongqiang Zhang; Xiaoqiang Tian; Xuanze Zhang; Ning Ma; Santosh Aryal; Farah Naz (International Journal of Climatology, 2023)
Understanding and exploring hydrological (H) or soil moisture (SM) drought due to meteorological (M) drought under changing climate is crucial for drought early warning. Previously, different methods were used to calculate drought propagation from one state (M to another [H or SM]). However, each method has its pros and cons and thus cannot describe appropriate propagation attributes. In this study, a time series analysis is carried out to explore the propagation process in the Yellow River Basin (YRB) and Hai River Basin (HRB) of China. Standardized Streamflow Index (SSI), Standardized SM Index (SSMI), and Standardized Precipitation Index (SPI) 1‐month time series were calculated using streamflow, satellite‐based SM, and precipitation from 1979 to 2016. The time series framework identifies the average drought propagation as 3.4–8.3 months (M–H) and 2.3–5 months (M–SM) in YRB, while 2.8–7.7 months (M–H) and 2.3–8.5 months (M–SM) in HRB. Cross‐wavelet analysis indicated that periodic characteristics of M drought are responsible for these droughts. Overall, the findings of this study may help to minimize the drought hazards posed by M droughts.

Detection and quantification of aflatoxins in spices stored in different food packaging materials - Muhammad Abrar; Samreen Ahsan; Muhmmad Nadeem; Atif Liaqat; Muhmmad Farhan Jahangir Chughtai; Muhammad Adil Farooq; Tariq Mehmood; Adnan Khaliq; Ayesha Siddiqa (Journal of Stored Products Research, 2023)

Thermal degradation characteristics, kinetic and thermodynamic analyses of date palm surface fibers at different heating rates - Abrar Inayat; Farrukh Jamil; Shams Forruque Ahmed; Muhammad Ayoub; Peer Mohamed Abdul; Muhammad Aslam; M. Mofijur; Zakir Khan; Ahmad Mustafa (Fuel, 2023)

Understanding the role of catchment and climate characteristics in the propagation of meteorological to hydrological drought - Hadush Meresa; Yongqiang Zhang; Jing Tian; Muhammad Abrar Faiz (Journal of Hydrology, 2023)

Hydrogen Production through Water Vapors using Optimized Corona-DBD Hybrid Plasma Micro-Reactor - Muhammad Younas; Sumeer Shafique; Abrar Faisal; Ainy Hafeez; Fahed Javed; Maria Mustafa; Fahad Rehman (Fuel, 2023)

A DFT Study on New Photovoltaic Dyes to Investigate their NLO Tuning at Near Infrared Region (NIR) as Pull–push Effect by End Capped Acceptors - Abrar U. Hassan; Sajjad H. Sumrra; Muhammad F. Nazar; Cihat Güleryüz (Journal of Fluorescence, 2023)

Linking Plants Functioning to Adaptive Responses Under Heat Stress Conditions: A Mechanistic Review - Mahmood Ul Hassan; Tassaduq Rasool; Chandni Iqbal; Adnan Arshad; Muhammad Abrar; Muhammad Mohsin Abrar; Muhammad Habib-ur-Rahman; Mehmood Ali Noor; Alam Sher; Shah Fahad (Journal of Plant Growth Regulation, 2022)

Nutritional Value of Dry Fish in Bangladesh and Its Potential Contribution to Addressing Malnutrition: A Narrative Review - Md. Hasan Al Banna; Abdullah Al Zaber; Nahidur Rahman; Md Abrar Mozahid Siddique; Muhammad Abu Bakr Siddique; John Elvis Hagan; M. A. Rifat; Christiana Naa Atsreh Nsiah-Asamoah; Abdul-Aziz Seidu; Bright Opoku Ahinkorah; Md Shafiqul Islam Khan (Fishes, 2022)
Understanding the linkage between the nutrient composition of foods and individuals’ recommended nutrient intake is important to address malnutrition. Despite it being a traditional and popular food item in Bangladesh, the nutrient composition of dry fish has not been reviewed yet. This study used a narrative review to assess the nutrient composition of dry fish and estimated its potential contribution to addressing some common nutritional deficiencies among children and pregnant and lactating women in Bangladesh. Records were collected from different databases, including the Web of Science, Google Scholar, PubMed, ScienceDirect, Banglajol, and ResearchGate. Data were extracted from 48 articles containing 1128 entries regarding nutrient composition. Most of the nutrient analyses estimated the proximate composition, whereas vitamin, mineral, amino acid, and fatty acid compositions were scarce in the literature. We found that dry fish has high protein and mineral content and could contribute highly to meeting the recommended nutrient intake of protein, iron, zinc, and calcium for children and pregnant and lactating women. The summarized nutrient composition data could be useful for further research to observe how dry fish could be best utilized to address malnutrition in Bangladesh. This narrative review recommends that further nutrient analysis, with emphasis on vitamin, mineral, and fatty acid compositions.

Structural and Electronic (Absorption and Fluorescence) Properties of a Stable Triplet Diphenylcarbene: A DFT Study - Abrar Ul Hassan; Ayesha Mohyuddin; Sohail Nadeem; Cihat Güleryüz; Sadaf Ul Hassan; Mohsin Javed; Muhammad Salman Muhsan (Journal of Fluorescence, 2022)

Moisture- and period-dependent interactive effects of plant growth-promoting rhizobacteria and AM fungus on water use and yield formation in dryland wheat - Muhammad Maqsood Ur Rehman; Ying Zhu; Muhammad Abrar; Wasim Khan; Wei Wang; Awais Iqbal; Anum Khan; Yuan Chen; Muhammad Rafiq; Muhammad Aammar Tufail; Jian-Sheng Ye; You-Cai Xiong (Plant and Soil, 2022)

The impact of COVID-19 pandemic on air pollution: a global research framework, challenges, and future perspectives - Khalid Mehmood; Sana Mushtaq; Yansong Bao; Saifullah; Sadia Bibi; Muhammad Yaseen; Muhammad Ajmal Khan; Muhammad Mohsin Abrar; Zaid Ulhassan; Shah Fahad; George P. Petropoulos (Environmental Science and Pollution Research, 2022)

Biochar increases salt tolerance and grain yield of quinoa on saline-sodic soil: multivariate comparison of physiological and oxidative stress attributes - Ghulam Abbas; Muhammad Mohsin Abrar; Muhammad Asif Naeem; Manzer H. Siddiqui; Hayssam M. Ali; Yantao Li; Khalil Ahmed; Nan Sun; Minggang Xu (Journal of Soils and Sediments, 2022)

Determinants of renewable energy sources in Pakistan: An overview - Umar Suffian Ahmad; Muhammad Usman; Saddam Hussain; Atif Jahanger; Maira Abrar (Environmental Science and Pollution Research, 2022)

New organosulfur metallic compounds as potent drugs: synthesis, molecular modeling, spectral, antimicrobial, drug likeness and DFT analysis - Abrar Ul Hassan; Sajjad Hussain Sumrra; Muhammad Nadeem Zafar; Muhammad Faizan Nazar; Ehsan Ullah Mughal; Muhammad Naveed Zafar; Mazhar Iqbal (Molecular Diversity, 2022)

Pollution characteristics and human health risk assessments of toxic metals and particle pollutants via soil and air using geoinformation in urbanized city of Pakistan - Khalid Mehmood; Yansong Bao; Roman Abbas; Saifullah; George P. Petropoulos; Hamaad Raza Ahmad; Muhammad Mohsin Abrar; Adnan Mustafa; Alwaseela Abdalla; Katia Lasaridi; Shah Fahad (Environmental Science and Pollution Research, 2021)

Knowledge, attitude, and practices associated with brucellosis among livestock owners and its public health impact in Punjab, Pakistan - Sabir Hussain; Abrar Hussain; Ubaid-ur-Rehman Zia; Syed Musa Raza Naqvi; Muhammad Yasir Zahoor; Muhammad Bilal; Jeffery HO; Olivier A. E. Sparagano (Biologia, 2021)

Processed animal manure improves morpho-physiological and biochemical characteristics of Brassica napus L. under nickel and salinity stress - Muhammad Naveed; Allah Ditta; Maryum Ahmad; Adnan Mustafa; Zulfiqar Ahmad; Manuel Conde-Cid; Shermeen Tahir; Syed Atizaz Ali Shah; Muhammad Mohsin Abrar; Shah Fahad (Environmental Science and Pollution Research, 2021)

Prediction of changes in water balance of Nam Co Lake under projected climate change scenarios - Muhammad Adnan; Shichang Kang; Muhammad Saifullah; Shiyin Liu; Guoshuai Zhang; Qiudong Zhao; Muhammad Abrar Faiz; Muhammad Zaman (Hydrological Sciences Journal, 2021)

Identification and inter‐comparison of appropriate long‐term precipitation datasets using decision tree model and statistical matrix over China - Muhammad Abrar Faiz; Yongqiang Zhang; Faisal Baig; Dariusz Wrzesiński; Farah Naz (International Journal of Climatology, 2021)
The reliability of long‐term precipitation estimates is vital for climatology and hydrometeorology applications. Different climatic zones and high rain gauge network (more than 800) of China are a suitable topography for performance evaluation of different long‐term precipitation datasets. In this study, seven long‐term precipitation datasets are tested against in situ observations at different time scales (1981–2016) at 813 grid points. Well‐known statistical indicators and Fast‐frugal tree (FFt) decision model are employed to identify the best long‐term datasets. Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks Climate Data Record is the only datasets that did not perform well in the study area. Asian Precipitation‐Highly‐Resolved Observational Data Integration Towards Evaluation (APHRODITE), Global Precipitation Climatology Centre (GPCC), and Climate Prediction Center (CPC‐Global) estimates are comparable with in situ observations. Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS), National Centers for Environmental Prediction (NCEP2) overestimate the precipitation extremes in the region. There exists a difference of 100–250 mm among precipitation datasets at an annual scale. All of the seven long‐term datasets underestimate the rxdays across China. The minimum range of rxdays (maximum precipitation amount in under defined days: 1 day or 5 days) captured by datasets is comparable except PERSIANN‐CDR. The maximum range calculated with PERSIANN‐CDR is 55.01 (rx1day), and 129.67 (rx5day), much less than the in situ rxdays. This analysis shows that datasets failed to capture maximum precipitation intensity in the region as well. FFt decision model results show that APHRODITE ranked first based on calculated consecutive dry days among all six other datasets in the most climatic zones. Overall, results indicate that data assimilation, the spatial coverage of ground stations, and interpolation techniques used to develop the datasets may limit the reliability of precipitation datasets in the study area.

Long-term fertilization alters chemical composition and stability of aggregate-associated organic carbon in a Chinese red soil: evidence from aggregate fractionation, C mineralization, and 13C NMR analyses - Adnan Mustafa; Xu Hu; Syed Atizaz Ali Shah; Muhammad Mohsin Abrar; Ali Akbar Maitlo; Kashif Ali Kubar; Qudsia Saeed; Muhammad Kamran; Muhammad Naveed; Wang Boren; Sun Nan; Xu Minggang (Journal of Soils and Sediments, 2021)

Assessment of the response of climate variability and price anomalies to grain yield and land use in Northeast China - Trinh Thi Viet Ha; Muhammad Abrar Faiz; Li Shuang (Environmental Science and Pollution Research, 2021)

Application of an improved multifractal detrended fluctuation analysis approach for estimation of the complexity of daily precipitation - Liangliang Zhang; Heng Li; Dong Liu; Qiang Fu; Mo Li; Muhammad Abrar Faiz; Shoaib Ali; Muhammad Imran Khan; Tianxiao Li (International Journal of Climatology, 2021)
Affected by climate change and high‐intensity human activities, the precipitation series is characterized by nonlinear complex fluctuations. In order to accurately quantify the precipitation complexity, the complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN) method was introduced to address the shortcomings of the traditional multifractal detrended fluctuation analysis (MFDFA), and the CEEMDAN‐MFFA method was proposed to explore the spatiotemporal variability and possible causes of precipitation complexity in Northeast China (NEC). The results showed that the traditional MFDFA method generally overestimated precipitation complexity. However, the CEEMDAN‐MFFA method improved the accuracy and reliability of precipitation complexity analysis. Daily precipitation series in NEC were characterized by multifractal with high uncertainty and anti‐persistence. The lowest precipitation complexity was 0.573, which appeared in Qian'an, Jilin Province, and the highest precipitation complexity was 1.108, which appeared in the Boketu, Inner Mongolia. The cities with high complexity of daily precipitation are sporadically distributed in the three provinces of Heilongjiang, Jilin and Liaoning. The average complexity is ~0.892, accounting for 22.5% of the total administrative districts. The complexity of daily precipitation showed a statistically insignificant downward trend with time. The precipitation dynamics structure in the southeast and northwest of the study area was complex, and the precipitation was less predictable than other regions. However, the precipitation dynamics structure was relatively simple and the precipitation was easily predictable in the northeastern, central and southwestern regions. Elevation, topographic relief, changes in water area, forest area and agricultural production were the main influencing factors for the differences in precipitation complexity. Results also revealed that increasing the area of forestland by means of protecting and breeding forests, via regulation of the forest ecosystems to alleviate the complex precipitation process will become a reliable approach to cope with nonstationary precipitation.

Correction to: In Silico Evaluation of Food Derived Bioactive Peptides as Inhibitors of Angiotensin Converting Enzyme (ACE) - Qudsia Yousafi; Jannat Batool; Muhammad Saad Khan; Tamsila Perveen; Muhammad Wasim Sajid; Abrar Hussain; Asim Mehmood; Shahzad Saleem (International Journal of Peptide Research and Therapeutics, 2021)

In Silico Evaluation of Food Derived Bioactive Peptides as Inhibitors of Angiotensin Converting Enzyme (ACE) - Qudsia Yousafi; Jannat Batool; Muhammad Saad Khan; Tamsila Perveen; Muhammad Wasim Sajid; Abrar Hussain; Asim Mehmood; Shahzad Saleem (International Journal of Peptide Research and Therapeutics, 2021)

Development of an integrated weighted drought index and its application for agricultural drought monitoring - Muhammad Ahmad Niaz; Muhammad Abrar Faiz; Wei Yongxia (Arabian Journal of Geosciences, 2021)

Carbon, nitrogen, and phosphorus stoichiometry mediate sensitivity of carbon stabilization mechanisms along with surface layers of a Mollisol after long-term fertilization in Northeast China - Muhammad Mohsin Abrar; Hu Xu; Tariq Aziz; Nan Sun; Adnan Mustafa; Muhammad Wajahat Aslam; Syed Atizaz Ali Shah; Khalid Mehmood; Baoku Zhou; Xingzhu Ma; Xianni Chen; Minggang Xu (Journal of Soils and Sediments, 2021)

SARS-CoV-2 nucleocapsid and Nsp3 binding: an in silico study - Muhammad Tahir Khan; Muhammad Tariq Zeb; Hina Ahsan; Abrar Ahmed; Arif Ali; Khalid Akhtar; Shaukat Iqbal Malik; Zhilei Cui; Sajid Ali; Anwar Sheed Khan; Manzoor Ahmad; Dong-Qing Wei; et al. (Archives of Microbiology, 2021)

Foliage application and seed priming with nitric oxide causes mitigation of salinity-induced metabolic adversaries in broccoli (Brassica oleracea L.) plants - Nudrat Aisha Akram; Naima Hafeez; Muhammad Farid-ul-Haq; Abrar Ahmad; Muhammad Sadiq; Muhammad Ashraf (Acta Physiologiae Plantarum, 2020)

Comparative Assessment of Reference Evapotranspiration Estimation Using Conventional Method and Machine Learning Algorithms in Four Climatic Regions - Ali Raza; Muhammad Shoaib; Muhammad Abrar Faiz; Faisal Baig; Mudasser Muneer Khan; Muhammad Kaleem Ullah; Muhammad Zubair (Pure and Applied Geophysics, 2020)

Soil and microbial biomass stoichiometry regulate soil organic carbon and nitrogen mineralization in rice-wheat rotation subjected to long-term fertilization - Muhammad Nadeem Ashraf; Cheng Hu; Lei Wu; Yinghua Duan; Wenju Zhang; Tariq Aziz; Andong Cai; Muhammad Mohsin Abrar; Minggang Xu (Journal of Soils and Sediments, 2020)

Effects of land use and climate variability on the main stream of the Songhua River Basin, Northeast China - Muhammad Abrar Faiz; Dong Liu; Qiang Fu; Faisal Baig; Ahmad Niaz; Tianxiao Li (Hydrological Sciences Journal, 2020)

Effects of Silicon and Phosphatic Fertilization on Rice Yield and Soil Fertility - Liying Wang; Umair Ashraf; Chunrong Chang; Muhammad Abrar; Xiong Cheng (Journal of Soil Science and Plant Nutrition, 2020)

An Integrated Systems Biology and Network-Based Approaches to Identify Novel Biomarkers in Breast Cancer Cell Lines Using Gene Expression Data - Abbas Khan; Zainab Rehman; Huma Farooque Hashmi; Abdul Aziz Khan; Muhammad Junaid; Abrar Mohammad Sayaf; Syed Shujait Ali; Fakhr Ul Hassan; Wang Heng; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2020)

Valorization of solid waste biomass by inoculation for the enhanced yield of biogas - Yasir Abbas; Farrukh Jamil; Sikander Rafiq; Moinuddin Ghauri; M. Shahzad Khurram; Muhammad Aslam; Awais Bokhari; Abrar Faisal; Umer Rashid; Sining Yun; Muhammad Mubeen (Clean Technologies and Environmental Policy, 2020)

Application of non-conventional soft computing approaches for estimation of reference evapotranspiration in various climatic regions - Ali Raza; Muhammad Shoaib; Afzaal Khan; Faisal Baig; Muhammad Abrar Faiz; Mudasser Muneer Khan (Theoretical and Applied Climatology, 2020)

GPT2 mutations in autosomal recessive developmental disability: extending the clinical phenotype and population prevalence estimates - Qing Ouyang; Brian C. Kavanaugh; Lena Joesch-Cohen; Bethany Dubois; Qing Wu; Michael Schmidt; Ozan Baytas; Stephen F. Pastore; Ricardo Harripaul; Sasmita Mishra; Abrar Hussain; Katherine H. Kim; et al. (Human Genetics, 2019)

Genetic polymorphism in association with susceptibility to tuberculosis: a study in a Pakistani population - AsmaGul Naz; Muhammad Assad Aslam; Abrar Ul Haq Khan; Sumaira Rasul; Hamid Manzoor; Rehana Iqbal; Ahmed Shehzad; Muhammad Ali (Brazilian Journal of Microbiology, 2019)

Assessment of precipitation variability and uncertainty of stream flow in the Hindu Kush Himalayan and Karakoram River basins of Pakistan - Muhammad Abrar Faiz; Dong Liu; Qiang Fu; Dariusz Wrzesiński; Shehakk Muneer; Muhammad Imran Khan; Tianxiao Li; Song Cui (Meteorology and Atmospheric Physics, 2019)

Ultrasonic seed treatment improved physiological and yield traits of rice under lead toxicity - Gangshun Rao; Umair Ashraf; Suihua Huang; Siren Cheng; Muhammad Abrar; Zhaowen Mo; Shenggang Pan; Xiangru Tang (Environmental Science and Pollution Research, 2018)

Behavioral activity patterns of adult and juvenile Greater Flamingos (Phoenicopterus roseus) with alteration of climatic pattern at Uchalli Lake, Punjab, Pakistan - Shabana Naz; Arnab Tanveer; Muhammad Abrar; Asma Ashraf (Environmental Science and Pollution Research, 2018)

Multifractal Detrended Fluctuation Analysis of Regional Precipitation Sequences Based on the CEEMDAN-WPT - Dong Liu; Chen Cheng; Qiang Fu; Chunlei Liu; Mo Li; Muhammad Abrar Faiz; Tianxiao Li; Muhammad Imran Khan; Song Cui (Pure and Applied Geophysics, 2018)

Determination of groundwater potential by using geoelectrical method and petrographic analysis in Rawalakot and adjacent areas of Azad Kashmir, sub-Himalayas, Pakistan - Abrar Niaz; Muhammad Rustam Khan; Umer Ijaz; Muhammad Yasin; Fahad Hameed (Arabian Journal of Geosciences, 2018)

Stream flow variability and drought severity in the Songhua River Basin, Northeast China - Muhammad Abrar Faiz; Dong Liu; Qiang Fu; Muhammad Uzair; Muhammad Imran Khan; Faisal Baig; Tianxiao Li; Song Cui (Stochastic Environmental Research and Risk Assessment, 2018)

Projection Pursuit Evaluation Model of Regional Surface Water Environment Based on Improved Chicken Swarm Optimization Algorithm - Dong Liu; Chunlei Liu; Qiang Fu; Tianxiao Li; Muhammad Imran Khan; Song Cui; Muhammad Abrar Faiz (Water Resources Management, 2018)

Application of gravity and magnetic methods for the crustal study and delineating associated ores in the western limb of Hazara Kashmir Syntaxis, Northwest Himalayas, Pakistan - Muhammad Rustam Khan; Shahid Saleem Bilali; Fahad Hameed; Awais Rabnawaz; Sohail Mustafa; Naveed Azad; Muhammad Basharat; Abrar Niaz (Arabian Journal of Geosciences, 2018)

Complexity measurement of precipitation series in urban areas based on particle swarm optimized multiscale entropy - Dong Liu; Chen Cheng; Qiang Fu; Yongjia Zhang; Yuxiang Hu; Dan Zhao; Muhammad Imran Khan; Muhammad Abrar Faiz (Arabian Journal of Geosciences, 2018)

Projected Changes of Future Extreme Drought Events under Numerous Drought Indices in the Heilongjiang Province of China - Muhammad Imran Khan; Dong Liu; Qiang Fu; Qaisar Saddique; Muhammad Abrar Faiz; Tianxiao Li; Muhammad Uzair Qamar; Song Cui; Chen Cheng (Water Resources Management, 2017)

Rainfall Extremes: a Novel Modeling Approach for Regionalization - Muhammad Uzair Qamar; Muhammad Azmat; Muhammad Adnan Shahid; Daniele Ganora; Shakil Ahmad; Muhammad Jehanzeb Masud Cheema; Muhammad Abrar Faiz; Abid Sarwar; Muhammad Shafeeque; Muhammad Imran Khan (Water Resources Management, 2017)

Recent Climate Trends and Drought Behavioral Assessment Based on Precipitation and Temperature Data Series in the Songhua River Basin of China - Muhammad Imran Khan; Dong Liu; Qiang Fu; Shuhua Dong; Umar Waqas Liaqat; Muhammad Abrar Faiz; Yuxiang Hu; Qaisar Saddique (Water Resources Management, 2016)

Analysis of the Appropriate Development Scale of Regional Paddy Field Under the Restriction of Water Resources - Dong Liu; Dan Zhao; Qiang Fu; Tianxiao Li; Muhammad Imran Khan; Wenting Liu; Faiz M. Abrar (Agricultural Research, 2016)

Precipitation variability assessment of northeast China: Songhua River basin - Muhammad Imran Khan; Dong Liu; Qiang Fu; Muhammad Azmat; Mingjie Luo; Yuxiang Hu; Yongjia Zhang; Faiz M Abrar (Journal of Earth System Science, 2016)

Petrology and geochemistry of Jura granite and granite gneiss in the Neelum Valley, Lesser Himalayas (Kashmir, Pakistan) - Muhammad Saleem Mughal; Muhammad Sabir Khan; Muhammad Rustam Khan; Sohail Mustafa; Fahad Hameed; Muhammad Basharat; Abrar Niaz (Arabian Journal of Geosciences, 2016)

Geotechnical study of marble, schist, and granite as dimension stone: a case study from parts of Lesser Himalaya, Neelum Valley Area, Azad Kashmir, Pakistan - Sohail Mustafa; Muhammad Arshad Khan; Muhammad Rustam Khan; Fahad Hameed; Muhammad Saleem Mughal; Aamir Asghar; Abrar Niaz (Bulletin of Engineering Geology and the Environment, 2015)

Geochemical and organic petrographic characteristics of low-rank coals from Thar coalfield in the Sindh Province, Pakistan - Abrar Ahmad; Mohammed Hail Hakimi; Muhammad Nawaz Chaudhry (Arabian Journal of Geosciences, 2015)

Aflatoxins: Biosynthesis, Occurrence, Toxicity, and Remedies - Muhammad Abrar; Faqir Muhammad Anjum; Masood Sadiq Butt; Imran Pasha; Muhammad Atif Randhawa; Farhan Saeed; Khalid Waqas (Critical Reviews in Food Science and Nutrition, 2013)

Problems encountered in bicistronic IRES-GFP expression vectors employed in functional analyses of GC-induced genes - Muhammad Mansha; Muhammad Wasim; Christian Ploner; Abrar Hussain; Asma Abdul Latif; Muhammad Tariq; Anita Kofler (Molecular Biology Reports, 2012)